Hypertensive Disorders of Pregnancy and Subsequent Cardiovascular Disease: Current National and International Guidelines and the Need for Future Research - Gamble, David T.; Brikinns, Bolanle; Myint, Phyo Kyaw; Bhattacharya, Sohinee (Frontiers in Cardiovascular Medicine, 2019)
Background: It is well-established that hypertensive disorders of pregnancy (HDP) are associated with an increased risk of cardiovascular disease (CVD) in later life. National and International guidelines recognize this but due to a lack of research in this area few details are provided on how best to risk stratify or when and how to monitor these women. Objectives: This article aims to summarize current guidelines in this area in order to raise awareness of need for further research in this important clinical area. Search Strategy: A review of the published literature was carried out in August 2018 using the databases EMBASE and Medline and the websites of professional societies were searched manually using the search terms “pre-eclampsia,” “hypertensive disorders of pregnancy,” “management,” “guidelines,” “long term follow up” and “cardiovascular risk.” Guidelines published in English were included and articles that provided guidance on follow up post-partum of women with HDP. Main Results: The search identified 360 records. Of these, 16 guidelines mentioned the follow up of women with HDP; their reported years ranges from 2010 to 2018. Only 8 (50%) provided some level of recommendation for follow up beyond the immediate post-partum period. These recognized the future risk of CVD to women from HDP and provide detailed recommendations for the management of these conditions during pregnancy and in the immediate post-partum period. Guidelines recommended that women and primary care clinicians are made aware of this risk and some suggest yearly BP monitoring, and at least 5 yearly monitoring of renal functions, urinalysis and lipid profile testing alongside lifestyle modifications and control of CVD risk factors. Guidelines used a combination of meta-analysis, individual cohort studies and expert opinions to inform their recommendations. Conclusions: There is a need for future studies of women with a history of HDP to define their trajectory for the development of CVD and candidate biomarkers in order to develop screening, risk stratification, and preventive measures to reduce the significant CV burden associated with HDP in women.